Whose Comatose Girlfriend? Figures of Crisis in Neoliberal Italy. Issue 1 (22nd March 2018) - Bassi, Serena
The Italian body politic has a long history of being "feminized": Italy has long been imagined through the metaphor of the nation as a woman both within and beyond national borders. The documentary Girlfriend in a coma is a recent example of this strategy: the film is based on the metaphor of Italy as a woman who has been beaten into a coma by a crass and criminal ruling class. In the film, Bill Emmott, who narrates, presents himself as Italy's disillusioned lover, who wishes to rescue her from the dramatic situation she is in. Implicitly, by arguing that Italy is a woman, Emmott stresses Italy's fragility and dependence on stronger cultures to save it. An apparent contradiction structures the film: on the one hand 'gender inequality' is one of the themes that the film foregrounds amongst the problems that Italy has to solve to get out of its 'coma', on the other, the films relies on a series of problematic cultural associations with woman as state of victimhood in order to make its case. The article will argue that the gendered metaphor in the film is instrumental in creating a cultural, social and economic programme, the goal of which is for Italy to move on from the economic crisis. Ultimately, by interrogating closely the apparent contradiction outlined above, it seeks to unpick the concept of 'gender equality' in this particular phase of capitalist progress and cast some light on what is intended exactly when the question of gender equality is invoked in contemporary debates on Italy's political and economic decline.